Analysis of the Influencing Factors of Consumers’ Purchase Intention of Online Knowledge Paid Products: The Case of China’s “De Dao” Application - Sun, Yi; Pongsakornrungsilp, Siwarit (Science, Technology, and Social Sciences Procedia, 2021)
In recent years, China’s mobile internet knowledge payment industry has developed rapidly. People’s attitude and consumption concept towards high-quality paid knowledge have changed, and their willingness to pay for high-quality content has become stronger. China’s knowledge paying users are increasing, and the industry market potential is huge. However, in the process of development, the knowledge payment platform has also encountered various problems in its development. For example, how to capture existing and potential users, what kind of network knowledge payment products users are willing to buy, and so on. In this paper, 410 valid questionnaires were collected based on consumer samples. Using the method of regression analysis, this paper empirically analyzes the influencing factors of consumers’ purchase intention to buy knowledge paid products from the perspective of user perception. Taking perceived usefulness, perceived entertainment, perceived cost and technical characteristics as independent variables and purchase intention as dependent variables, a factor model affecting the purchase intention of knowledge paid products is designed. This paper proves that perceived usefulness, perceived entertainment, perceived cost and technical characteristics are positively correlated with purchase intention. Finally, this paper provides some reference suggestions for the development of knowledge payment platform represented by Dedao.